Exploring diverse supramolecular tessellation through hierarchical assemblies of nonalternant nanographene - Jian Sun; Ziqi Deng; David Lee Phillips; Junzhi Liu (Proceedings of the National Academy of Sciences, 2025)
Tessellation, as an ancient and fascinating mathematical pursuit, has not only captivated mathematicians but also has attracted chemists’ increasing attention at the molecular level in recent years. Exploring tessellation at the molecular scale is pivotal for gaining profound insights into the effects of tessellation on materials and elucidating the essential design principles for supramolecular tessellation. In this study, we develop a dynamic fullerene host ( 1 ) with three consecutive heptagons, which promotes diverse supramolecular tessellation via hierarchical assembly. In the solid state, molecule 1 arranges itself into a layered square-shaped tessellation in the crystal superstructure. Interestingly, the co-crystal structures of 1 with C 60 and C 70 exhibit highly ordered triangular and rhombic tessellation patterns, respectively, due to the adaptive regulation of heptagons with different curved guests, demonstrating the first series of layered tessellated framework in supramolecular fullerene chemistry. This work not only enriches the development of in-solution supramolecular tessellation but also facilitates the rational design of tessellated 2D layered molecular materials